MR Imaging of the Corpus Callosum in Pediatric Patients with Neurofibromatosis Type 1 - Dubovsky, Elizabeth C.; Booth, Tim N.; Vezina, Gilbert; Samango-Sprouse, Carole A.; Palmer, Kathryn M.; Brasseux, Cynthia O. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Many pediatric patients with neurofibromatosis type 1 (NF-1) have an apparent increased thickness of the corpus callosum (CC) on sagittal T1-weighted images compared with patients not affected by NF-1. In this study, we compared the surface area of the CC in children with NF-1 with that of healthy pediatric control subjects to determine if this was another common intracranial manifestation of NF-1.METHODS: Midsagittal T1-weighted MR images of 43 consecutive children with NF-1 and 43 age- and gender-matched healthy control subjects were reviewed retrospectively. The surface area of the CC and the midsagittal intracranial skull surface (MISS) area were measured five times each on all midsagittal images. A mean CC to mean midline intracranial surface area ratio (CC/MISS) was calculated for each.RESULTS: There is a statistically significant increase in the mean CC surface area in pediatric patients with NF-1 (680 mm2 ±98, range 509–974 mm2) compared with control subjects (573 mm2 ± 83, range 404–797 mm2). The mean MISS is significantly increased in patients with NF-1 (16568 mm2 ± 1161, range 14107–19394 mm2 vs 15402 mm2 ± 1133, range 12951–17905 mm2 for control subjects). CC/MISS was also significantly increased in the patients with NF-1 relative to the control subjects (.0410 ± .0043, range .0330–.0530 vs .0372 ± .0043, range .0270–.0470 for control subjects).CONCLUSION: A larger midsagittal surface area of the CC is another intracranial manifestation of NF-1 that can be demonstrated by sagittal MR imaging. The etiology is unclear, but could be related to abnormal neurofibromin and Ras protein activity. Potential clinical relevance is discussed herein.